Improved Perinatal Depression Screening, Treatment, and Outcomes With a Universal Obstetric Program. Issue 5 (May 2016) - Avalos, Lyndsay A.; Raine-Bennett, Tina; Chen, Hong; Adams, Alyce S.; Flanagan, Tracy
Abstract : OBJECTIVE: To evaluate whether universal prenatal and early postnatal screening for depression leads to increased detection, subsequent intervention, and improved depressive symptom outcomes. METHODS: We conducted a population-based retrospective cohort study of 97, 678 pregnant Kaiser Permanente Northern California members during three phases of the Universal Perinatal Depression Screening Program (preimplementation, rollout, fully implemented) from 2007 through 2014. Depression screening scores (Patient Health Questionnaire-9), depression diagnoses, individual counseling visits, demographic characteristics, and medication dispensings were extracted from electronic health records and pharmacy databases. The percentage of women screened, new depression diagnoses, and women receiving treatment were compared among the three phases (tests of trend). Changes in depressive symptom scores up to 6 months postpartum were assessed (rollout and fully implemented phases). RESULTS: A significant increase emerged in the percentage of women screened over the three phases ranging from less than 1% (n=122) (preimplementation) to 98% (n=41, 124) (fully implemented) ( P <.001). Identification of a new depression diagnosis increased from 8.2% (n=1, 341) (preimplementation) to 11.5% (n=4, 943) (fully implemented) ( P <.001). Although the observed percentage of women receiving treatment decreased (60.9% [preimplementation] to 47.1% [fully implemented]), significant increases in the expected percentage of women receiving treatment emerged (42.6% [preimplementation] to 47.1% [fully implemented]; P <.05). Similar trends were noted for women with Patient Health Questionnaire-9 scores of 15 or greater (greater severity), highlighting an increase in expected percentage of women receiving treatment (5.9% [preimplementation] to 81.9% [fully implemented]; P <.05). In the fully implemented phase, improvements in depressive symptoms up to 6 months postpartum were noted. CONCLUSION: These data provide evidence of benefit for universal perinatal depression screening programs regarding depression identification and treatment receipt and suggest improvement in symptom outcomes for women in screening programs, especially among integrated health care systems. Abstract : Universal perinatal depression screening in obstetric care is associated with increased identification of depressive symptoms, depression treatment and improved symptom outcomes.